Entre passos e vozes: percepções de espaços e patrimônios no sítio ferroviário de Santa Maria, RS - Faccin, Danielle (2014)
Santa Maria, in the state of Rio Grande do Sul, is a city whose urban development has been strongly influenced by the presence of the railway and the activities associated to it, directly or indirectly, since the end of 19th century. With the termination of railway activities engendered by the federal government in the 1990s, the Railroad Site of Santa Maria, located in the central region of the city, has undergone a process entailing the abandonment of the site, the heritagization of urban spaces and real estate, and, subsequently, a program of urban revitalization which continues to be in progress currently. In this context, the objective of this thesis is to understand how the residents of the Railroad Site of Santa Maria have perceived the transformations of this urban space over the last twenty years. By employing an ethnographic method, consisting of direct observations in the streets and interviews with residents of the Railroad Site in 2012 and 2013, it was possible to identify conflicts and convergences between the daily city practices and the actions undertaken by public agencies. Likewise, it was possible to discern transformations and continuities in the ways that residents have used spaces and heritages and produced representations of the Railroad Site of Santa Maria, in addition to identifying modes of recognition and appropriation of material remnants of the railway as a historical and cultural heritage of Santa Maria and Rio Grande do Sul.